Mikrozonasi Frekuensi Dominan (F0) dan Faktor Amplifikasi (A0) Di Desa Pacarejo Bagian Barat, Semanu, Gunungkidul, Yogyakarta - SALSABIILA ANINDYA NOOR CANDRANINGTYAS; Susanti, Dwi Budi (Jurnal Stasiun Geofisika Sleman, 2024)
Yogyakarta is a region with high seismic activity influenced by the interaction of the Indo-Australian and Eurasian plates and the presence of local faults. One of the areas significantly affected is Pacarejo Village, Semanu District, Gunungkidul, which experienced damage from the June 30, 2023 earthquake with a magnitude of M6.0. This study aims to conduct microzonation of predominant frequency (f0) and amplification factor (A0) in the area using the Horizontal to Vertical Spectral Ratio (HVSR) method based on microtremor analysis as an earthquake disaster mitigation effort. A total of 19 measurement points were conducted to determine the f0 and A0 values. The analysis results indicate that f0 values range from 1.46 to 11.04 Hz, with higher values in the southern part of the study area, reflecting hard and thin rock layers. In contrast, lower values indicate thick and soft sediment layers. The A0 values range from 1.07 to 3.4, predominantly classified as low to moderate. The highest A0 value was found near earthquake-affected houses, reflecting the interaction between soil characteristics and seismic wave amplification. The resulting microzonation maps of predominant frequency and amplification factor provide an overview of the area's seismic characteristics. These findings are expected to serve as a basis for earthquake disaster mitigation in Pacarejo and its surroundings and support safer and more sustainable development planning.